The human ABCG2 transporter engages three gates to control multidrug extrusion - Narakorn Khunweeraphong; Karl Kuchler (iScience)
Summary: The human ABCG2 transporter plays roles in physiological detoxification across barriers and in anticancer multidrug resistance. The translocation pathway for drug extrusion and its gating mechanism remains elusive. Here, we demonstrate that the ABCG2 multidrug transporter holds two cavities that are delineated by three regulatory gates, indicating a substrate translocation channel. Drugs are trapped in the central cavity after entering through the pivotal intracellular entry gate. This flexible cavity is surrounded by a cluster of three highly conserved phenylalanines. Their aromatic side chains enact a “clamp-push-seal” motion to ensure unidirectional substrate movement. The unique residues T435 and N436 act as critical selectors for ligands, determining the broad substrate specificity. The upper cavity is covered by the lid architecture, constituting the final gate before multidrug extrusion. This work unravels deep mechanistic details on how the translocation channel utilizes pivotal gating steps, including the sequence of events that drive ABCG2-mediated multidrug efflux.